UJI STABILITAS CHECK DAM KEDUNGREJO 15 DI KALI KONTO KECAMATAN PUJON KABUPATEN MALANG - Suhudi Suhudi; ester ria dwi kandari (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
Cactment area Kali Konto is the part of up stream Brantas which is located in Pujon Malang It’s 233 km2. The main building water that’s located at DAS Brantas Hulu is Selorejo reservoir. It’s ethnic age reach 100 years but will be reduced because the silting up of reservoir. It’s caused of the big erotion and sedimentation in the water arrest area. The erotion happened more than the limit of tolerance from the land erotion whichs is permitted. Kali Konto is the biggest sedimentation contributor for Selorejo Reservoir. One of the action in case erotion and sedimentation in the river is by building Sediment Controller Building or generally mentioned by Check Dam. From the calculation stated that the dimension of check dam will be made of river stone like the elevation of top spillway peak dam main in 862 m with effectife height amount of 4 m and foundation depth amount of 2 m, the width of mercu pelimpah main dam amount of 3 m with discharge in the repeatance periode is 50 years amount of 1186,79 m3/sec, the controlling height amount of 1 m. The analytic of building stability check dam is in the safe condition, it is 1,27 1,2 (required).